Augmented Reality–Supported Learning and Its Effect on Secondary Students’ Conceptual Mastery of Geometry at Nanyang Girls' High School - Wei Ling Tan; Siti Aishah (Journal of Science and Mathematics Education, 2026)
Mathematics education, particularly in the domain of three-dimensional geometry, often demands high-level spatial visualization skills, posing a significant cognitive barrier for many secondary students. Conventional teaching methods relying on two-dimensional representations are frequently insufficient to elucidate spatial complexities. Augmented Reality (AR) technology offers an innovative pedagogical solution by projecting virtual objects into the real environment, bridging the gap between abstract representations and concrete understanding. This study aims to empirically evaluate the effectiveness of AR-supported learning on geometry conceptual mastery among students at Nanyang Girls' High School. The research employed a quasi-experimental design with pre-test and post-test measures on non-equivalent control groups. Participants comprised secondary level students divided into two groups: an experimental group utilizing AR applications to interactively visualize, manipulate, and dissect geometric solids, and a control group using traditional text-and-image-based learning media. Assessment instruments focused on deep conceptual understanding of solid properties, geometric transformations, and spatial relationships. Statistical analysis revealed a significant difference in the mean post-test score improvement of the experimental group compared to the control group ($p < 0.05$). These findings indicate that the interactive visualization features offered by AR effectively assist students in constructing more accurate mental models and achieving stronger memory retention of complex geometric objects. Beyond cognitive gains, qualitative data also noted increased student motivation and active engagement during the exploration process. This study concludes that AR integration is a valid instructional strategy for enhancing geometry mastery and recommends the development of mathematics curricula that are more adaptive to immersive technologies at the secondary level.